Jan Długosz jako kronikarz dziejów Podniestrza w I połowie XII wieku = Jan Długosz as chronicler of the history of the Podniestrze region in the 1st half of the 12th century - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article Jan Długosz as chronicler of the history of the Podniestrze region in the 1st half of the 12th century presents an analysis of the message contained in Długosz?s Annals dealing with the political situation in the south-eastern borderland of Rus? and with the political and dynastic contacts between those ruling there and the Piast dynasty. The Annals of Jan Długosz represent an important source of information about Rus? history as well as about the relations between Poland and Rus? in the Middle Ages. In the light of the information provided in the Annals the history of region of Podniestrze during the rule of Rostislav of Tmutarakan?s descendants seem especially interesting. The very essence of Długosz?s reports is based on the fact that Długosz became a depositary of information which cannot be found in any other sources identified so far.
Keywords: Długosz, Jan (1415-1480); Podniestrze; 12 w.